2011
DOI: 10.4038/josuk.v3i0.2741
|View full text |Cite
|
Sign up to set email alerts
|

Studies on antioxidant activity of Indian Gooseberry fruit and seed

Abstract: Fruits and seeds of Indian Gooseberry (Phylanthus emblica, S. Nelli) were investigated to evaluate their antioxidant activity. Antioxidant activity was evaluated by the estimation of peroxide values (PV) of shark liver oil, treated with fruit and seed extracts incubated at 60 0 C for a period of nine days. Seed extracts showed higher antioxidant activity than fruit extracts. The ethanol and ethyl acetate extracts of the fruit and all extracts of the seed were found to have higher antioxidant activity than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
1
13
0
1
Order By: Relevance
“…Concentrations of 1.14 ± 0.20 and 1.44 ± 0.03 mg/g, fresh weight was obtained on day 9 and day 12 of studies for control and coated guava fruits, respectively. Increase in phenolic contents may be related to increased antioxidant activity (Nadeesha et al 2007). Ascorbic acid concentration increased during the storage of Lalit guava fruit in both control and coated samples (Fig.…”
Section: Chemical Analysis Of Fruitsmentioning
confidence: 99%
“…Concentrations of 1.14 ± 0.20 and 1.44 ± 0.03 mg/g, fresh weight was obtained on day 9 and day 12 of studies for control and coated guava fruits, respectively. Increase in phenolic contents may be related to increased antioxidant activity (Nadeesha et al 2007). Ascorbic acid concentration increased during the storage of Lalit guava fruit in both control and coated samples (Fig.…”
Section: Chemical Analysis Of Fruitsmentioning
confidence: 99%
“…24 grams of leaf powder were placed with care in the thimble and fixed firmly to the condenser. About 200ml of distilled water was used as a solvent, taken in the round bottom flask [7,8]. The total apparatus were positioned in the heater and a temperature not more than the boiling point of the solvent was maintained.…”
Section: Preparation Of Extracts I Non Fermented Extractmentioning
confidence: 99%
“…Studies have demonstrated that plant phenolics as a major source of natural antioxidants. The fruit of Indian Gooseberry (Emblica officinalis [EO]) is rich in Vitamin C and it acquires maximum antibacterial and antioxidative activities [5]. The unique antioxidants such as Gallic acid, Vitamin C, ß-carotene, and SOD enzyme have been reported to be present in the fruit.…”
mentioning
confidence: 99%
“…The unique antioxidants such as Gallic acid, Vitamin C, ß-carotene, and SOD enzyme have been reported to be present in the fruit. Various studies have shown the antioxidant property of EO in various forms of its extractions (ethanol and methanol) [5,6].…”
mentioning
confidence: 99%